2002
DOI: 10.1902/jop.2002.73.11.1313
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Matrix Metalloproteinases in Cyclosporin‐Treated Gingival Fibroblasts Is Regulated by Transforming Growth Factor (TGF)‐β1 Autocrine Stimulation

Abstract: The data presented here suggest that TGF-beta1 in an autocrine fashion may contribute to a reduction of proteolytic activity of human gingival fibroblasts in CsA-induced gingival overgrowth, which favors the accumulation of extracellular matrix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
60
0
3

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 55 publications
4
60
0
3
Order By: Relevance
“…The rat model associated with primary cultures of human gingival fibroblast treated with CyA was chosen on the basis of our previous experiments to mimic the CyA-induced gingival overgrowth seen in humans. 5,6,12 The main finding of the present study was that myofibroblast transdifferentiation is not induced by CyA, even with CyA stimulating TGF-β1 expression. Furthermore, we were able to demonstrate that CTGF expression levels were unaffected by CyA, suggesting a reason for the lack of myofibroblast transdifferentiation.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…The rat model associated with primary cultures of human gingival fibroblast treated with CyA was chosen on the basis of our previous experiments to mimic the CyA-induced gingival overgrowth seen in humans. 5,6,12 The main finding of the present study was that myofibroblast transdifferentiation is not induced by CyA, even with CyA stimulating TGF-β1 expression. Furthermore, we were able to demonstrate that CTGF expression levels were unaffected by CyA, suggesting a reason for the lack of myofibroblast transdifferentiation.…”
Section: Discussionmentioning
confidence: 51%
“…7,8,23,24 The regulatory cytokine TGF-β1 has been traditionally considered an inducer of the myofibroblast phenotypes both in vivo and in vitro. 25 Since CyA induces gingival overgrowth in the presence of fibroblasts characterized by the synthesis of elevated levels of TGF-β1, 5,6 we evaluated the effects of CyA on transdifferentiation of gingival fibroblasts to myofibroblasts. The rat model associated with primary cultures of human gingival fibroblast treated with CyA was chosen on the basis of our previous experiments to mimic the CyA-induced gingival overgrowth seen in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have showed that TGF-β1 may play a role in drug-induced GO [19][20][21][22]. Recent studies support the theory that CsA increases the level of TGF-β1 in GCF samples from CsA-treated patients [23].…”
Section: Introductionmentioning
confidence: 64%
“…Although the present experiments cannot determine whether angiotensin II regulates MMP-2 and MT1-MMP expression directly or indirectly through TGF-␤ 1 , there is a recent report showing the negative regulation of MMP-1 and MMP-2 by TGF-␤ 1 in human gingival fibroblasts. 34 In conclusion, increases in local generation of angiotensin II and expression of AT 1 receptors in coronary vessels observed at the insulin-resistant stage of NIDDM in OLETF rats 18 appear to modulate coronary expression of ECMrelated molecules and lead to coronary matrix remodeling, possibly associated with overproduction of TGF-␤ 1 . This …”
Section: Discussionmentioning
confidence: 85%